Optimización del proceso productivo en el área de post cosecha en la florícola “Nevado Ecuador”. - Chipugsi Albán, Ariel Sebastián (2021)
This project consists of developing an optimization model for the production of flower bunches boxes in the company "NEVADO ECUADOR", to minimize and improve the product elaboration process in the post-harvest area; where a set of sequential activities was established, starting with a mapping of the current production process, identifying each activity immersed in the process, with the help of measurement tools, the execution times of each activity were controlled, in order to know the average, normal and standard times of these activities, where a time study was carried out in order to optimize the production process of said area, since it is the area with the greatest work delays. For this optimization model, tools such as the Study of Production Times will be used, these techniques allow to collect, measure and evaluate the data that will be obtained from the study that is going to be carried out. Achieving in this way to improve the productive efficiency of the floriculture and contributing to the continuous improvement of the process.